2015
DOI: 10.1007/s11606-015-3184-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Residents Lack Comfort and Experience with Alcohol Screening and Brief Intervention: A Multi-Site Survey

Abstract: BACKGROUNDApproximately one in six adults in the United States (U.S.) binge drinks. The U.S. Preventive Services Task Force recommends that primary care physicians screen patients for such hazardous alcohol use, and when warranted, deliver a brief intervention.OBJECTIVEWe aimed to determine primary care residents’ current practices, perceived barriers and confidence with conducting alcohol screening and brief interventions (SBI).DESIGNThis was a multi-site, cross-sectional survey conducted from March 2010 thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 36 publications
1
27
0
3
Order By: Relevance
“…In this sense, national 2,11,14,16 and international 20,[22][23] authors have pointed out the efficacy of this model of brief intervention performed by professionals working in primary health care. Therefore, the present study emphasizes the importance of the qualification of the health professionals that develop their activities in primary health care in the FHS in order to provide a better service to people with problems related to alcohol and other drugs welcomed at the health system gateway.…”
Section: 14-15mentioning
confidence: 97%
See 2 more Smart Citations
“…In this sense, national 2,11,14,16 and international 20,[22][23] authors have pointed out the efficacy of this model of brief intervention performed by professionals working in primary health care. Therefore, the present study emphasizes the importance of the qualification of the health professionals that develop their activities in primary health care in the FHS in order to provide a better service to people with problems related to alcohol and other drugs welcomed at the health system gateway.…”
Section: 14-15mentioning
confidence: 97%
“…Authors have been pointing out religiosity as a protective factor against the consumption of drugs, [18][19][20] reinforcing that religiosity remains a protective factor against the use of psychoactive substances, both licit and illicit. In this context, it is possible to infer that religion may represent a strength in the sense of helping the professional of the Family Health team to develop preventive actions for the community in partnership with the churches in the covered area in the planning of educational actions for health.…”
Section: 14-15mentioning
confidence: 99%
See 1 more Smart Citation
“…(D'Amico, Paddock, Burnam, & Kung, 2005; McKnight-Eily, Liu, Brewer, Kanny, Lu, Denny et al, 2014) Further, primary care residents have been shown to lack comfort and experience with alcohol screening and brief intervention. (Le, Johnson, Seale, Woodall, Clark, Parish et al, 2015) Barriers to screening and counseling include competing priorities, lack of provider training, misconceptions about patient comfort with discussing alcohol, and lack of appropriate infrastructure and protocols. To address these shortcomings, we sought to develop and implement, using quality improvement techniques, a systematic approach to screening and counseling primary care patients for unhealthy alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is a field to develop actions on early identification, preventive actions and health promotion. (8,9) Studies show the need for identifying the pattern of consumption of psychoactive substances in the population served, mainly in PHC, to provide them with the required level of care, information about the damages resulting from the use of these substances, assisting the prevention of diseases caused by consumption. (9)(10)(11)(12) In the context of problems related to the use of alcohol and other drugs, and due to short national literature on the topic, the authors would like to emphasize that this is a different study because it understands religiosity relevance as an additional element to prevent diseases and to assist the actions implemented in the practice of health professionals.…”
Section: Introductionmentioning
confidence: 99%